The α-helix alignment of proteins in water solution toward a high-frequency electromagnetic field: A FTIR spectroscopy study. (3rd July 2017) - Calabrò, Emanuele; Magazù, Salvatore
ABSTRACT: The aim of this article was to study the effects of mobile phone electromagnetic waves at 1750 MHz on the Amide I and Amide II vibration bands of some proteins in bidistilled water solution by means of Fourier transform infrared (FTIR) spectroscopy and Fourier self-deconvolution (FSD) analysis. The proteins that were used for the experiment were hemoglobin, myoglobin, bovine serum albumin and lysozyme. The exposure system consisted of microwaves emitted by an operational mobile phone at the frequency at 1750 MHz at the average power density of 1 W/m 2 . Exposed and control samples were analyzed using FTIR spectroscopy and FSD analysis. The main result was that Amide I band of the proteins that were used increased significantly ( p < 0.05) after 4 h of exposure to MWs, whereas Amide II band did not change significantly. This result can be explained assuming that the α-helix structure of the proteins aligned itself with the direction of the electromagnetic field due to the alignment of C = O stretching and N − H bending ligands that are oriented along with the α-helix axis that give rise to the Amide I mode.